Biomaterials : a basic introduction - Chen, Qizhi, 1963-; Thouas, George (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Biomaterials is a multidisciplinary subject, involving materials science, engineering, cell biology, and medicine. This textbook therefore provides an appropriate balance between depth and broadness of coverage, sufficient to enable understanding of the most important concepts and principles at the right level by students from a wide academic spectrum. This project has been developed from extensive lecture notes created by Dr. Chen in the teaching of biomaterial at Monash U, since 2008.'--
Biomaterials science and engineering -- Toxicity & corrosion -- Mechanical properties of biomaterials -- Metallic biomaterials in orthopaedic implants -- Metallic biomaterials : miscellaneous others -- Bioinert ceramics -- Bioactive and bioresorbable ceramics -- Polymeric biomaterials : fundamentals -- Bioinert polymers -- Bioresorbable polymers -- Medicine and medical science -- Anatomy & human disorders I -- Anatomy & human disorders II -- Anatomy & human disorders III -- Cells and biomolecules -- Histology and tissue properties I -- Histology and tissue properties II -- The immune system & body responses to biomaterials -- Evaluation of biomaterials -- Regulation of medical devices.
Includes bibliographical references and index.
Keywords: Biocompatible materials; Bioengineering -- methods; Prostheses and Implants